2014
DOI: 10.1097/gme.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Risk of long-term hot flashes after natural menopause

Abstract: Objectives To estimate the risk of hot flashes relative to natural menopause and evaluate associations of hormone levels, behavioral and demographic variables with the risk of hot flashes following menopause. Methods Annual assessments of 255 women who were premenopausal at baseline and reached natural menopause during 16 years of follow-up. Results The prevalence of moderate/severe hot flashes increased in each premenopausal year, reaching a peak of 46% in the first two years after the final menstrual per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(115 citation statements)
references
References 34 publications
5
93
0
6
Order By: Relevance
“…From the results in table 1, the EG showed non-significant improvement in systolic and diastolic blood pressure (SBP/DBP), and resting heart rate by 5.8L%, 3.6L% and 2.6L% respectively. These are in congruence with other studies that reported significant improvement in blood pressure following aerobic exercise (Ammar, In another study, regular aerobic exercise lasting 12 weeks contributed to significant reductions in resting blood pressure of postmenopausal women (Ellen W. Freeman et al, 2015). In a study to determine the effects of daily walking on lowering blood pressure in postmenopausal women that lasted 24 weeks, there were significant reductions in systolic blood pressure (Freeman et al, 2010).…”
Section: Resultssupporting
confidence: 74%
“…From the results in table 1, the EG showed non-significant improvement in systolic and diastolic blood pressure (SBP/DBP), and resting heart rate by 5.8L%, 3.6L% and 2.6L% respectively. These are in congruence with other studies that reported significant improvement in blood pressure following aerobic exercise (Ammar, In another study, regular aerobic exercise lasting 12 weeks contributed to significant reductions in resting blood pressure of postmenopausal women (Ellen W. Freeman et al, 2015). In a study to determine the effects of daily walking on lowering blood pressure in postmenopausal women that lasted 24 weeks, there were significant reductions in systolic blood pressure (Freeman et al, 2010).…”
Section: Resultssupporting
confidence: 74%
“…In further studies of placebo effects, a second control group that is not given either active medication or placebo could better address the question of regression to the mean. Although the mean natural duration of menopausal hot flashes is considerable, ranging from about 4 years to more than 10 years (31), and participants were selected for stable ratings of hot flashes in the screen period, it is possible that variations in hot flash frequency could account for placebo improvement. It should also be noted that one protocol required a relatively high frequency of hot flashes in the screen period, suggesting the possibility that subsequent decreases were a return to more usual levels of hot flashes or that hot flashes improved with time for reasons other than the direct effects of study pills.…”
Section: Discussionmentioning
confidence: 99%
“…13 Up to 80% of women experience VMS during the MT, 4,5 and most rate them as moderate to severe. 6 Vasomotor symptoms are one of the chief menopause-related problems for which US women seek medical treatment. 7,8 Results from the Study of Women’s Health Across the Nation (SWAN) suggest that VMS are also independently associated with multiple indicators of elevated cardiovascular risk 9,10 and greater bone loss and higher bone turnover.…”
mentioning
confidence: 99%